Successful Non-Surgical Root Canal Treatment on Auto-Transplanted Maxillary Premolar with Apical Periodontitis - Christopher M. Naglieri; Ellie Bash; Glen A. Karunanayake; Carlos H. R. Camargo; Takashi Komabayashi (Case Reports in Dentistry)
Auto-transplantation is a procedure that replaces traumatized or congenitally missing teeth. While most auto-transplanted teeth are successfully integrated into recipient sites, the donor tooth may develop apical periodontitis, causing early failure. In the present case report, the periodontic resident performed the procedure on a 15-year-old male by selecting donor teeth #4 and #13 and transplanting them at recipient sites #29 and #20, respectively. After 6 weeks, the patient was referred to the endodontic resident for evaluation of tooth #20 due to symptom development. While one auto-transplanted tooth (donor tooth #4, recipient site #29) was successfully integrated, the other (donor tooth #13, recipient site #20) was unsuccessful: the patient was diagnosed with pulp necrosis and a chronic apical abscess. Because of the patient’s age, collaboration among periodontic, endodontic, and orthodontic residents/specialists informed the clinical decision to pursue non-surgical root canal treatment (NSRCT) rather than extraction. The canal was cleaned and shaped to a size #80 using copious irrigation of 2.5% sodium hypochlorite (NaOCl), followed by 17% ethylenediaminetetraacetic acid (EDTA) via the EndoVac Negative Pressure Irrigation system. The tooth was dried with paper points, and then calcium hydroxide was mixed with 2.5% NaOCl and placed with an amalgam carrier 2 mm from the radiographic apex. The tooth was next temporized with Teflon tape and Fuji TRIAGE. Four weeks later, after confirming the patient was asymptomatic and tooth mobility had decreased, the canal was obturated using EndoSequence Bioceramic Root Repair Material Fast Set Putty in 2 mm incremental layers to achieve a three-dimensional fill and create an apical plug to prevent gutta-percha extrusion, then backfilled in incremental layers of gutta-percha to the cementoenamel junction (CEJ). At the 8-month follow-up, the patient was asymptomatic, and the periodontal ligament (PDL) had no signs of periapical pathology. When teeth undergoing auto-transplantation procedures develop apical periodontitis, NSRCT can be implemented.